Elaboración de pan labranza utilizando harina de torta de sacha inchi (plukenetia volubilis) como sustitución parcial de harina de trigo (triticum aestivum) y evaluación de su calidad - Zavaleta Sandoval, Marilu (2013)
The aim of the present work was to analyze the effect of the incorporation of the flour of Sacha lnchi's cake and the time of kneaded on the sensory and nutritional characteristics of the bread tillage far it the characteristics were evaluated organolépticas, chemical analysis proximal as well as the ideal percentage of substitution and the microbiological analysis. The sample of Sacha lnchi's cake (P/ukenetia volubilis), it is proceeding from the locality of San Miguel of Ria In May district of Muds (Region San Martin), which was obtained across the company Tropical Jungle Exports E.l.R.L. in charge of the processing and extraction of the oil of the seed. The chemical analysis proximal of the cake of sacha inchi threw the fallowing results: Dampness 11.20%, Protein 41.5%, Fat 21.30 %, Ash 4.76 %, Fiber 14.44 %, Carbohydrates 6.80% with an apparent density of 1.14 g/cm3, pH of 6.15 and one acidity of 0.026 % expressed as sulphuric acid. Far the obtaining of the flour of Sacha lnchi's cake preliminary tests were realized of dried using a dryer with traffic of warm air, being the experimental bullfights to 4 temperatures (60, 80, 100, 120ºC), turning out to be the temperature of 120ºC in 15 minutes the one that achieved the decrease of the astringency. The chemical analysis proximal far the flour were the fallowing enes: dampness 5.42 %, protein 32.05 %, fiber 3.7 %, ash 4.36 %, fat 22.09 %, carbohydrates 32.39 %, pH of 5.7%, andan acidity of 0.0327 % (as sulphuric acid). The operations that followed far the operation of bread tillage replaced with flour of cake of sacha inchi were the following enes: Formulation - Mixed I kneaded - Cut/ mold - Fermented - Baked and Cooled. There was analyzed the effect of the different percentages of substitution and time of kneaded on the general characteristics of the breads and specially in texture, flavor, specific volume and acceptability. Tests that the formulation allowed to select to óbtain breads with ideal sensory and nutritional characteristics. In the selected formulation there was replaced 20% of the flour of wheat with flour of Sacha lnchi's Cake in the mass panaria, bringing a percentage of dampness of 40.12 and of total proteins of 14.23%, managing to improve nutricionalmente the mass panaria. Being corroborated in the multifaceted score effected theoretically. The chemical calculation decided, in function to the digestibility of the protein of a theoretical way for the different mixtures which use the method recommended by the committee FAO I WHO I UNO, (1985) of a boss aminoacidico of the protein of the milk of cow as protein of reference. In the sensory evaluation the judges selected the bread tillage to 20 % of substitution the one that was presenting better characteristics texturables and was not changing the typical flavor of the bread, obtaining a multifaceted score of 68 % for students, value that is alike the recommended for the commission of the CODEX ALIMENTARIUS FAO/OMS 1972-1983 which indicates that for the development and growth of the children 70 % is needed and for the maintenance up to 50% of the multifaceted score which the obtained product is suitable for this end. The obtained bread presented the following nutritional characteristics: dampness 24.75 %, Protein 12.18 %, Fat 6.03 %, Ash 2.07 %, Fiber 1.63 %, Carbohydrates 53.34 % and a microbiological quality that is inside the standards allowed by the national procedure.